Acessibilidade web móvel para usuários cegos: checklist para websites do comércio eletrônico - Costa, Levi Cadmiel Amaral da (2021)
The web, as well as mobile devices, represent technological advances that have changed the ways in which information is created and made available in society, causing large information flows to emerge through the advances provided by technology. While these advances provide some social groups with more flexible experiences on the web, other parts of society are at risk of exclusion, including the blind population. In this context, the general objective of the present investigation is to examine the necessary requirements for the development of a mobile web accessibility checklist for blind users in order to have better experiences on ecommerce websites. It is a research that, in terms of its approach, adopts qualitative and quantitative aspects. Regarding the objectives of the investigation, it is classified as descriptive. With regard to data collection instruments, the questionnaire is adopted as a way to validate an initial version of the checklist composed of 19 questions based on the evaluation of Information Science researchers who have published on accessibility on the web in the period covered between 2010 and 2020. The theoretical framework is based on two thematic axes. In the first, issues related to blind users, accessibility and technology are presented, specifically with regard to the web and mobile devices. In the second, concepts and characteristics that are associated with electronic commerce are presented, presenting issues related to origin, operations in Brazil, particularities associated with mobile devices and brief notes on accessibility and mobile commerce. From the validation of the checklist through the evaluation of the research participants, one question was excluded, ten were changed, eight were kept without the need for adjustments and four new questions were included. Among the recommendations of the survey respondents, the following can be mentioned: include concepts and / or parameters, point out that the blind user benefits from mobile devices through their memorization and practical experience with these devices, avoid subjectivity, mix questions that complement each other, avoid questions that address aspects already addressed in previous issues, among other issues. It is concluded that the developed checklist can benefit users with blindness in the sense that such a tool can be used to check if the structures of e-commerce websites are in accordance with the informational needs of people with blindness when they try to interact with these websites for through mobile technology, in addition, it is concluded that the checklist may be useful for web designers, for researchers who investigate accessibility, for specialists who develop e-commerce websites, as well as for any and all professionals interested in developing the mobile web in an inclusive way.